Camu-camu (Myrciaria dubia): Tropical fruit of excellent functional properties that help to improve the quality of life - Arellano-Acuña, Ericka (2016)
Camu camu is the fruit that has the highest content of vitamin C, which is 100 times higher than the lemon. This tropical fruit is native to the Amazon region and it is mainly distributed in Bolivia, Brazil, Colombia, Ecuador, Peru and Venezuela. In its composition, it has different bioactive compounds such as carotenoids, antioxidants, vitamins and phenolic compounds such as anthocyanins and tannins that give it the characteristics of a functional food. It also has beneficial properties on the health of those who consume it, because it is considered a powerful antioxidant, anti-inflammatory and antimicrobial; it is also a great ally against cardiovascular diseases and for people suffering from obesity. Research shows a positive effect for the treatment of early stages of diabetes, as well as providing other benefits. This review work aimed to study the literature regarding camu-camu as a functional food that contributes to improve the quality of life due to its positive impact on health.